Politics a unified introduction to how democracy works - Budge, Ian (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2019)
"This comprehensive introduction to politics provides an essential template for assessing the health and workings of present day democracy by exploring how democratic processes bring public policy into line with popular preferences. Incorporating the latest findings from Big Data across the world, it provides a crucial framework showing students how to deploy these for themselves, providing straightforward, practical orientation to the scope and methods of modern political science. Key features: Everyday politics is explained through concrete applications to democracies across the world; Predictive theories illuminate what goes on at various levels of democracy; Outlines, in easy to understand terms, the basic statistical approaches that enable empirically-informed analysis; Rich textual features include chapter summaries, reviews, key points, illustrative briefings, key concepts, project and essay suggestions, relevant reading all clearly explained in 'How to Use This Book'; Provides a firm basis for institutional and normative approaches to democratic politics; Concluding section reviews other approaches to explaining politics, assessing their strengths and weaknesses. Politics is an essential resource for students of political science and of key interest to economics, public policy analysis and more broadly the social sciences"-- Provided by publisher